How Can Psychological Capital Influence Student Career Adaptability? - Purwaningrum, Shinta; Setiowati, Arum; Ernawati, Ika (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The objectives and aims of this research are (1) to determine the Psychological Capital profile of students from the Guidance and Counseling Study Program Batch 2021 at PGRI University Yogyakarta, (2) to determine the Career Adaptability profile of students from the Guidance and Counseling Study Program Batch 2021 at PGRI University Yogyakarta, and (3) to investigate whether there is a significant influence between Psychological Capital and Career Adaptability among students from the Guidance and Counseling Study Program Batch 2021 at PGRI University Yogyakarta. The population in this study is students from the Guidance and Counseling Study Program. The research method used is correlational quantitative. The instruments used in this research are two types of questionnaires, namely the Psychological Capital questionnaire and the Career Adaptability questionnaire. These questionnaires will be tested for validity and reliability. Hypothesis testing uses correlational testing. The research results show that the average level of Psychological Capital and Career Adaptability of students in the Guidance and Counseling study program of the 2021 cohort at PGRI University Yogyakarta is in the very high category, and there is a positive and significant influence between Psychological Capital and Career Adaptability of students in the Guidance and Counseling study program of the 2021 cohort at PGRI University Yogyakarta at a level of 0.557, which is classified as moderate